Cycle more with virtual reality: a proof of concept study in an institutionalised able-bodied geriatric population. (1st March 2021) - Loggia, Gilles; Gauthier, Antoine; Lemiere, Fabrice; Drigny, Joffrey; Desvergee, Antoine; Leconte, Pascale; Ruet, Alexis
Abstract: Background/Objectives: Physical activity (PA) has significant benefits for older adults. However, the recommended PA is rarely achieved in nursing homes. In this proof of concept study, we assessed whether virtual reality (VR) could help to increase spontaneous PA during a stationary cycling session. Design: Prospective crossover proof of concept study. Setting: Nursinghome. Participants: Twelve participants (10 men) aged 63–88, able-bodied but with moderate cognitive impairment. Intervention: TWO stationary cycling sessions with and withoutVR. Measurements: Cycling distance, pedalling duration, average speed, mean pedalling cadence and the modified Borg rating of perceived exertion scale. Results: Cycling distance and duration were significantly higher in the VR condition. Most participants would rather repeat cycling sessions with VR than without. Conclusion: The use of VR seems feasible to help achieve PA recommendations for able-bodied people living in nursing homes, even with moderate cognitive impairments.